Analisis Kesepadanan Makna Terjemahan Surah Al-Fatihah Qur’an Kemenag Menggunakan Tinjauan Metode Semantik - Haykal Nabil; Lubbi Muhammad Abdallah (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2023)
Arabic is a language that has a rich meaning, because of that many people are still wrong in interpreting the meaning in Arabic. This makes translation in a word not worth it. In translating text from SL to TL it is not arbitrary, there are 8 strategies in translating ST to TT, namely: word-to-word translation, literal translation, faithful translation, semantic translation, communicative translation, idiomatic translation, free translation, adaptation translation. Various strategies are used to find meanings that are in accordance with SL. This research will discuss the equivalence analysis of the translation of surah Al-Fatihah from the Ministry of Religion's Qur'an in 2022 in terms of semantic studies. This research was conducted using a descriptive qualitative approach. The results of this study state that the translation of the Al-Qur'an of the Ministry of Religion in 2022 in surah Al-Fatihah has many equivalents, but there are still discrepancies in meaning in this translation, both lexical and grammatical meanings, therefore it must be re-equipped, so that it is more compatible with the method semantic translation translation.